2016
DOI: 10.1038/icb.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Cornea lymphatics drive the CD8+ T‐cell response to herpes simplex virus‐1

Abstract: Herpes simplex virus type 1 (HSV-1) infection of the cornea induces vascular endothelial growth factor (VEGF)-A-dependent lymphangiogenesis. However, the extent to which HSV-1-induced corneal lymphangiogenesis impacts the adaptive immune response has not been characterized. Here, we used floxed VEGF-A mice to study the importance of newly created corneal lymphatic vessels in the host adaptive immune response to infection. Whereas the mice infected with the parental virus (strain SC16) exhibited robust corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Persistent lymphatic vessel hyperplasia results following chronic respiratory tract infection with mycoplasma pulmonis, resulting in bronchial lymphedema, and airflow obstruction (Baluk et al, 2005; Yao et al, 2010), and sustained inflammation following Yersinia pseudotuberculosis infection induces lymphatic leakage, insufficient dendritic cell (DC) trafficking, and persistently compromised canonical mucosal immunity (Fonseca et al, 2015). Furthermore, corneal herpes simplex 1 (HSV-1) infection induces lymphangiogenesis driven by the expression of vascular endothelial growth factor A (VEGF-A) from infected corneal epithelial cells (Wuest and Carr, 2010), leading to enhanced antigen drainage and CD8 + T cell immunity (Gurung et al, 2016). We therefore hypothesized, that in the context of active viral replication in non-lymphoid tissue, contextual cues influence regional lymphatic vessel function, downstream immune induction, and host viral defense.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent lymphatic vessel hyperplasia results following chronic respiratory tract infection with mycoplasma pulmonis, resulting in bronchial lymphedema, and airflow obstruction (Baluk et al, 2005; Yao et al, 2010), and sustained inflammation following Yersinia pseudotuberculosis infection induces lymphatic leakage, insufficient dendritic cell (DC) trafficking, and persistently compromised canonical mucosal immunity (Fonseca et al, 2015). Furthermore, corneal herpes simplex 1 (HSV-1) infection induces lymphangiogenesis driven by the expression of vascular endothelial growth factor A (VEGF-A) from infected corneal epithelial cells (Wuest and Carr, 2010), leading to enhanced antigen drainage and CD8 + T cell immunity (Gurung et al, 2016). We therefore hypothesized, that in the context of active viral replication in non-lymphoid tissue, contextual cues influence regional lymphatic vessel function, downstream immune induction, and host viral defense.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies from other researchers have shown that antigen‐specific CD8 + T cells are critical in preventing HSV‐1 lytic cycle activation in the trigeminal ganglia (TG), the anatomical site where the virus establishes a latent infection for the lifetime of the host 3 . Now in the current study, 1 Gurung et al 1 have further demonstrated that corneal LG is indispensable to evoke a CD8 + T‐cell‐mediated immune response against the HSV‐1 infection. The authors employed an ingenuous method to specifically suppress corneal LG upon HSV‐1 infection.…”
mentioning
confidence: 75%
“…In a new study by Gurung et al 1 published in this issue of Immunology and Cell Biology , the authors described how corneal lymphangiogenesis (LG) can influence the activation of the adaptive immune system against herpes simplex virus type 1 (HSV‐1) infection (Figure 1). Previous studies from these authors have investigated the role of HSV‐1 infection in triggering VEGF‐A‐dependent neovascularization in mouse cornea 2 .…”
mentioning
confidence: 99%
“…This interaction may be fortified by LYVE‐1, as glycosylated LYVE‐1 binds FGF2 tightly, and in fact, soluble LYVE‐1 inhibits FGF2‐mediated lymphangiogenesis . However, inhibition of FGF2 in targeted therapies must be executed carefully to avoid possible toxicities; for example, FGF2 is involved in neurogenesis and its inhibition may impair nerve regeneration . Furthermore, FGF2 and VEGF‐C were shown to work synergistically to promote tumor growth and metastasis to the lung via blood vessels and to sentinel lymph nodes via lymphatic vessels in a mouse model of fibrosarcoma .…”
Section: Lymphangiogenesis Mechanisms: Major Target Sitesmentioning
confidence: 99%
“…193 However, inhibition of FGF2 in targeted therapies must be executed carefully to avoid possible toxicities; for example, FGF2 is involved in neurogenesis and its inhibition may impair nerve regeneration. 80,194 Furthermore, FGF2 and VEGF-C were shown to work synergistically to promote tumor growth and metastasis to the lung via blood vessels and to sentinel lymph nodes via lymphatic vessels in a mouse model of fibrosarcoma. 192 Together, these studies support the advantage of combination therapies that inhibit both FGFR and VEGFR-3 signaling to therapeutically target pathologic lymphangiogenesis.…”
Section: Fgf and Pdgf Pathwaysmentioning
confidence: 99%